2015
DOI: 10.1063/1.4927611
|View full text |Cite
|
Sign up to set email alerts
|

Bonding between graphene and MoS2 monolayers without and with Li intercalation

Abstract: We performed density functional theory (DFT) calculations for a bi-layered heterostructure combining a graphene layer with a MoS2 layer with and without intercalated Li atoms. Our calculations demonstrate the importance of the van der Waals (vdW) interaction, which is crucial for forming stable bonding between the layers. Our DFT calculation correctly reproduces the linear dispersion, or Dirac cone, feature at the Fermi energy for the isolated graphene monolayer and the band gap for the MoS2 monolayer. For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In addition, a recent theoretical work found that intercalated lithium ions enhances the binding energy through orbital hybridizations between cations (lithium ions) and anions (MoS 2 ) (ref. 32). Second, the intercalated lithium donates electrons to MoS 2 , which changes the oxidation states of Mo, and hence the electronic properties of MoS 2 (refs 33, 34).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent theoretical work found that intercalated lithium ions enhances the binding energy through orbital hybridizations between cations (lithium ions) and anions (MoS 2 ) (ref. 32). Second, the intercalated lithium donates electrons to MoS 2 , which changes the oxidation states of Mo, and hence the electronic properties of MoS 2 (refs 33, 34).…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that MoS 2 /GR heterostructure exhibits markedly better electrochemical kinetic compared with MoS 2 /GR hybrid, well agreeing to the results of the CV measurement. The superior electrochemical kinetic of MoS 2 /GR heterostructure should be ascribed to the important role of MoS 2 /GR heterointerfaces in increasing the electronic conductivity of MoS 2 , enlarging the adsorption energy of Li‐ion on the surface of MoS 2 layer, and maintaining the high diffusion mobility of Li‐ion . Furthermore, the ultrasmall MoS 2 nanosheets can effectively shorten the Li‐ion transport path with more active sites for Li‐ion adsorption and reaction .…”
Section: Resultsmentioning
confidence: 99%
“…The superior electrochemical kinetic of MoS 2 /GR heterostructure should be ascribed to the important role of MoS 2 /GR heterointerfaces in increasing the electronic conductivity of MoS 2 , enlarging the adsorption energy of Li-ion on the surface of MoS 2 layer, and maintaining the high diffusion mobility of Li-ion. [26][27][28][29][30] Furthermore, the ultrasmall MoS 2 nanosheets can effectively shorten the Li-ion transport path with more active sites for Li-ion adsorption and reaction. [36] In addition, it is noteworthy that the MoS 2 /GR heterostructure delivers an enhanced specific capacity than MoS 2 /GR hybrid at the low current density, even higher than the theoretical value of pure MoS 2 (167 mAh g À 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations